2015
DOI: 10.15644/asc49/1/5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Hinge Axis Transfer Modality on the ThreeDimensional Condylar Shift Between the Centric Relation and the Maximum Intercuspation Positions

Abstract: Adresa za dopisivanjeRobert Ćelić Sveučilište u Zagrebu Stomatološki fakultet Zavod za mobilnu protetiku Gundulićeva 5, 10 000 Zagreb Tel: 1 4802 111 celic@sfzg.hr Sažetak Svrha: Željelo se odrediti utječe li način registracije i prijenosa šarnirske osi (prijenos obraznim lukom spram prosječnog montiranja) s ispitanika u artikulator na trodimenzionalni pomak kondila između položaja centrične relacije (CR) i maksimalne interkuspidacije (MI). Materijal i metode: U istraživanju su sudjelovala 32 potpuno ozubljena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
(9 reference statements)
2
1
0
Order By: Relevance
“…Dimensional measurements of the TMJ joint spaces were considered indicative of condyle movement potential 44 . The PJS was greater than the AJS in all three groups except the crossbite side of the UCG, and the SJS was the largest joint space in all three groups, which is in agreement with Leonardi et al 23 In the UCG, the AJS was slightly smaller on the non‐crossbite side, and the SJS was slightly larger on the non‐crossbite side.…”
Section: Discussionsupporting
confidence: 85%
“…Dimensional measurements of the TMJ joint spaces were considered indicative of condyle movement potential 44 . The PJS was greater than the AJS in all three groups except the crossbite side of the UCG, and the SJS was the largest joint space in all three groups, which is in agreement with Leonardi et al 23 In the UCG, the AJS was slightly smaller on the non‐crossbite side, and the SJS was slightly larger on the non‐crossbite side.…”
Section: Discussionsupporting
confidence: 85%
“…It has been suggested that the position of the condyles concerning the posterior walls of the glenoid fossa is more asymmetric in unilateral malocclusion than normal occlusion 36 . The dimension of TMJ joint space can be indicative of the condylar movement potential 37 . A most recent study showed that the patients with unilateral chewing preference had more anterior condyles than those without, 38 which might account for our findings.…”
Section: Discussionsupporting
confidence: 49%
“…36 The dimension of TMJ joint space can be indicative of the condylar movement potential. 37 A most recent study showed that the patients with unilateral chewing preference had more anterior condyles than those without, 38 which might account for our findings. To enhance the accuracy and reliability of our results, we assessed the relative condylar position within the mandibular fossa using another method and obtained the same results.…”
Section: Ta B L Ementioning
confidence: 52%
“…This requires the use of a facebow and an articulator to record the patient's occlusal relationship, which is called occlusal transfer. The spatial relationship of the maxilla and mandible can be recorded and adjusted in vitro [ 6 ]. The clinical importance of the use of facebows is controversial because there is no evidence to support that their use leads to better clinical outcomes [ 7 ].…”
Section: Introductionmentioning
confidence: 99%